The Effect of Qris Transaction Volume and Nominal Value on Indonesia's Economic Growth for the Period 2020-2024 - Annisa Desfikasari; Vicy Andriany; Mariana Puspa Dewi; Mohammad Aliman Shahmi (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study examines the effect of QRIS transaction volume and nominal value on Indonesia's economic growth from 2020 to 2024. The rapid increase in QRIS usage, reaching 6.24 billion transactions worth IDR 659.9 trillion in 2024, motivated this research. A quantitative field research approach was employed, using documentation techniques from Bank Indonesia, ASPI, and BPS annual reports. Multiple linear regression analysis with SPSS 25 was conducted. The results show that QRIS transaction volume and nominal value do not have a significant effect on Indonesia's economic growth during the study period. The R-square value of 0.045 indicates that only 4.5% of economic growth variation can be explained by both variables, while 95.5% is influenced by other factors. These findings suggest that the substitution effect dominates QRIS transactions, primarily relocating existing transactions rather than creating new economic activity.